POSSIBILITIES OF PROGRAM COMPLEX FOR PLANNING OF IMPULSIVE TECHNOLOGIES BY THE METHOD OF «NEXT-DOOR NEIGHBOUR» - Владимир Васильевич Третьяк; Антон Виталиевич Онопченко; Анастасия Сергеевна Федорова (Авіаційно-космічна техніка та технологія, 2019)
In aircraft and engines details are used for implementation of difficult functions: providing of bearing strength of knots and good on the whole; differentiations of different environments – working and surrounding, having different parameters on pressure, temperature, closeness, speed, providing of minimum losses at the flowline around by threads of different environments and etc Power functions in most cases execute the details of obolochkovoy form or inflexibilities flat with elements, and functions of differentiation of environments – details with the channel surfaces. The given details can be made methods of the impulsive stamping. A program complex is developed, allowing to design impulsive technologies by the method of «next-door neighbour». Data about details are presented at a few informative levels – level of general form, fragments and additional elements, relief and exactness. At level general form to present data about details as an aggregate of three basic components: bottom, walls and flanets. On the given components fragments are executed and additional elements, perceiving loading, and also local elements for placing and fastening in them of sensors, devices, key units. A program complex allows to use a few possible variants of planning: without the change of structure of analogue and parametricheskoy tuning (method of the complete borrowing of analogue); without the change of structure of analogue (method of borrowing of analogue with the parametricheskoy tuning); with the change of structure of analogue. At the near analogue of detail a revision in analogue is taken mainly to adjustment of the modes of treatment. In default of such, a few analogues are used, and all analogue is exposed to the revision and its structural units on the basis of synthesis of new technological decisions. For the tract steady in production of land of details with the near designer-technological properties a model technological process is created for the complex detail, in which are reflected basic to the aggregate of surfaces and their elements, characteristic for all tract of land. In the program a few algorithms are used of search of «next-door neighbour».  Algorithms are used to the program on the Evklid distance, on the square of Evklid distance, on the distance Chebisheva and sedate distance Minkovskogo. Basic algorithms are presented, screen forms of program complex and possibilities of program complex.